Enhancing Sustainable Business Practices: Triple-Layer Business Model Canvas Analysis of SEGITIGA Coffee - Fita Kurniasari; Mahardika Agung Madepo; Ariya Naím (IECON: International Economics and Business Conference, 2025)
This study explores how an MSME is able to develop its business sustainability. The increasing concern for environmental issues by consumers makes coffee shops need to take steps to accommodate this. This research focuses on a coffee shop, SEGITIGA Coffee, in Pontianak city that has been operating for 9 years by modifying its business model. This study combines PESTEL environmental scanning with IFE-EFE strategic analysis to refine the Triple Layer BMC model. The study captures first-hand perspectives from coffee shop entrepreneurs through in-depth qualitative research conducted during September-November 2024. The study found that SEGITIGA Coffee has successfully implemented initial eco-friendly practices—leveraging digital tools and recycled materials—demonstrating its commitment to sustainability. However, significant untapped potential remains, as these efforts operate below optimal efficiency and impact. This study demonstrates that strategic partnerships with external stakeholders can enhance SEGITIGA Coffee’s sustainability performance. By systematically integrating eco-friendly practices into its core business model, the company can not only reduce its environmental footprint but also differentiate itself in an increasingly eco-conscious market. These improvements are not merely operational upgrades but represent a transformative opportunity to future-proof the business. This research helps small businesses adopt sustainability while staying profitable. It offers practical solutions for entrepreneurs, supports policymakers creating green business programs, and aids researchers studying sustainable models in developing economies.